РАЗВИТИЕ ГЕПАТОЦЕЛЛЮЛЯРНОЙ КАРЦИНОМЫ В ИСХОДЕ ХРОНИЧЕСКОЙ ДЕЛЬТА-ИНФЕКЦИИ - Л. Ю. Ильченко; Т. В. Кожанова; К. К. Кюрегян; А. А. Сарыглар; О. Н. Сарыг-Хаа; Я. Д. Сонам-Байыр; М. И. Михайлов (Архивъ внутренней медицины, 2014)
Hepatocellular carcinoma is 95% of the total malignant liver tumors. Total 318 patients with chronic delta infection, indigenous inhabitants of the Republic of Tyva, were examined. 121 patients were observed in dynamic (2009–2012). CHD was diagnosed in 77.4% (246/318) cases, LCD — in 22.6% (72/318) cases. Progression of CHD in LCD was showed in 10.7% (13/121), decompensation of LC — in 14% (17/121) and development of HCC — in 6.6% (8/121) patients, observed in 2009–2012. All patients with HCC were young working age (43.5 ± 8.4 years). The diagnosis of HCC was estimated in all patients on late stage when there are multiple lesions in the liver (by ultrasound data and CT). Replication of hepatitis viruses were estimated in 4 of 8 HCC cases: HDV RNA was detected in 2 patients, HBV DNA — in 1 patient, replication of both viruses (HBV DNA + HDV RNA) —  in 1 person. One patient with HCC and confirmed replication of HBV, HDV died due to bleeding from varicose veins in the esophagus and stomach.Conclusion. HCC in the outcome of CHD are formed in minority patients due to rapid disease progression, development of LC decompensation and its complications (coma, bleeding) with a high frequency of deaths.